SIFAT FISIK DAN MEKANIK PAPAN PARTIKELDARI KAYU SENGON (PARASERIANTHES FALCATARIA. L) DAN SERBUK SABUT KELAPA (COCOS NUCIFERA.L) - Roza, Dewi; Dirhamsyah, M.; haida, Nur (Universitas Tanjungpura, 2015)
This research aims to utilize the low quality of wood i.e.sengon (Paraserianthes falcataria) and waste of Coconut fiber dust to made particle board. Particle board made with different ratio i.e 100% sengon, 80% sengon and 20% Ccocnut fiber with adhesive concentration of 12%, 14% and 16%. Particle board made with size 30 cm x 30 cm x 1 cm with a density of 0,6 g/cm3 at a pressure of 25 kg/cm2 at 1400C for 8 minutes. Evaluated the physical properties (density, water content, water absorption and thickness swelling) and mechanical properties modulus of elastis (MOE), modulus of rupture (MOR) and internal bonding (IB) was conducted in accordance with JIS A 5908-2003 standard. The results showed that the density value sranged between 0.53g/cm3 - 0.58g/cm3, water contentranged from 6.63%-8.27%, thickness swelling ranged between7.51% -11.75%,water absorption ranged between 53.75% - 64.62%, MOE ranged between 14654.54 kg/cm2 - 18031.95 kg/cm2, MOR ranged between 169.54kg/cm2 - 218.47 kg/cm2, internal bonding ranged from3.33 kg/cm2-4.93 kg/cm2. The particle board values can fulfill the standart of JIS A 5908-2003, except for the value of the MOE. Composition of raw materials significantly affect the water absorption value, MOE and MOR mean while the concentration of adhesive significantly affect the value of thickness swelling, water absorption, MOE and MOR. Interaction between the ratio of raw material and concentration of adhesive did not significantly affect the physical and mechanical properties of particle board. The best values of particle board was achieved with composition sengon 80% and 20% coconut fiber dust withan adhesive concentration 16%. Keyword : Coconut fiber, paraserianthes falcataria, particle board, physical, mechanical properties.